ORAL COMMUNICATION STRATEGIES USED IN PERFORMING SPEECH BY TEENAGERS OF “ENGLISH MASSIVE” PROGRAM KEDIRI - Tsania Ainurrahma (Graduate Program, University of Islam Malang, 2021)
This study explored at describing what oral communication strategies used in aspeech performance by teenagers of English Massive Program Kediri andanalyzing speaking challenges encountered during communication as well thestrategies used to manage with communication breakdowns. During the speechperformance and interview, the strategies were investigated to solve students'problems. The study used a qualitative approach, which includedquestionnaires, observation, and interviews. The participants were 10 teenagers’finalist of speech competition held by English Massive Program. The datacollection was accomplished for three months. The results demonstratelinguistic and non-linguistic issues that students confronted during speechperformance. Following the data analysis, the students increased their use ofsocial affective strategy more often than other strategies. This study suggestsprovided language learners’ attention on positive strategies may contribute tolearners’ speaking performance.